Automatic Music Boundary Detection Using Short Segmental Acoustic Similarity in a Music Piece. (14th July 2008) - Itoh, Yoshiaki; Iwabuchi, Akira; Kojima, Kazunori; Ishigame, Masaaki; Tanaka, Kazuyo; Lee, Shi-Wook
Abstract : The present paper proposes a new approach for detecting music boundaries, such as the boundary between music pieces or the boundary between a music piece and a speech section for automatic segmentation of musical video data and retrieval of a designated music piece. The proposed approach is able to capture each music piece using acoustic similarity defined for short-term segments in the music piece. The short segmental acoustic similarity is obtained by means of a new algorithm called segmental continuous dynamic programming, or segmental CDP. The location of each music piece and its music boundaries are then identified by referring to multiple similar segments and their location information, avoiding oversegmentation within a music piece. The performance of the proposed method is evaluated for music boundary detection using actual music datasets. The present paper demonstrates that the proposed method enables accurate detection of music boundaries for both the evaluation data and a real broadcasted music program.